COMPARISON OF COLORIMETRIC AND CHEMILUMINESCENT ELISA TESTS FOR DETECTION OF IgG ANTIBODIES TO HUMAN EPO IN THE SERA OF EXPERIMENTAL ANIMALS - A. M. Kudryashova; N. A. Mikhailova; O. V. Borisova (Медицинская иммунология)
Production of antibodies to erythropoietin-stimulating drugs is an important problem of therapy with recombinant human erythropoietin (EPO). It leads to changes in the pharmacokinetic profile and decreased therapeutic efficiency. Upon long-term treatment with EPO preparations, neutralizing antibodies can result in rare cases, thus leading to complete pure red cell aplasia. Hence, detection of antibodies to EPO is an important stage in the assessment of the drug immunogenicity in preclinical and clinical studies, as well as during the treatment with EPO. We have compared colorimetric and chemiluminescent ELISA tests for detection of IgG antibodies to human EPO with 3,3’,5,5’-tetramethylbenzidine – hydrogen peroxide and luminol -hydrogen peroxide detection systems, respectively. Аntibodies to human EPO were determined in blood serum samples of experimental animals, i.e., rabbits and guinea pigs following their immunization withdifferent doses of pegylated human recombinant EPO-beta subcutaneously or intravenously. The affinitypurified rabbit polyclonal antibodies to human EPO were used as a reference material. The effects of hydrogen peroxide and luminol concentrations upon sensitivity of a chemiluminescent method were also studied. We have shown a 1.5-2-fold increase in sensitivity when using 4-iodophenol for amplification of chemiluminescence. A comparison of the chemiluminescence intensity with time has demonstrated a better stability for the substrate mixture prepared on borate buffer. A decrease in chemiluminescence signal with time was proportional to the decrease in background signal, thus rendering stability of the signal/background ratio for 3 to 30 minutes. Due to optimizing the substrate mixture composition and conditions of chemiluminescence recording, the reached detection limits for colorimetric and chemiluminescent ELISA’s were, respectively, 0.6 ng/ml and 0.08 ng/ml. The measurement range was extended by more than 20 times for chemiluminescent ELISA. The chemiluminescent ELISA for anti-erythropoietin antibody detection showed a 1.9 to 2.6-fold increase in sensitivity for rabbit serum, and 1.8 to 8.9-fold for guinea pigs serum. Good correlation of results was found for quantitative detection of antibodies in rabbit sera using the two methods (R = 0.981). Thus, chemiluminescent ELISA allowed develop a more sensitive detection technique of IgG antibodies to human erythropoietin.